The returned - Mott, Jason (Mott, Jason. Returned, 2013)
When their son Jacob, who died tragically at his 8th birthday party in 1966, arrives on their doorstep, still 8 years old, Harold and Lucille Hargrave must navigate a strange new reality as chaos erupts around the world as people's loved ones are returned from beyond.